NEW METHOD FOR EVALUATING GIBBS FREE ENERGYIN SHAPE MEMORY ALLOYS - Makdisi, Matti; Al -Shadidi, Zina (Iraqi Journal of Science, 2024)
Smart materials or shape memory alloys have a wide range of importantapplications in our time, They are used in the medical field, the main partsthat are used in surgical operations by computers made of these materials,because of unique properties of this kind of alloys where it canautomatically retrieve forms and accurately with the change of ambienttemperature or with the change of pressure imposed on it or a magnetic field(or electric) Surrounding. Thus, it becomes possible for a specialist to givethe desired shape during the development of the alloy in the vicinity of atemperature equal to the temperature of the human body and then pull thisalloy from the oven then in room temperature it will have the ingot formwould facilitate the introduction into the patient's body through the events ofwound smaller than if the process was conducted through regular, As inmodern operations to widen the arteries and directed by gravel from thekidneys eliminate malignant tumors and other surgical procedures other. Asalso used in manufacturing aircraft wings where the wing changes shapewith changing temperatures of the upper atmosphere. Also used in the verysmall motor industry because of the ability of its molecules to interact withthe surrounding magnetic field or by changing the pressure imposed on it.A new way for the evaluation of the Gibbs free energy for the shapememory alloys at any point within the specimen at the end of thetransformation is developed.In contrast with our previous model , which is limited in practice tothe whole specimen , this model is valid for length scales specified bythe a, b, c for the parent and the emberio lattice and controlled by thetransformation matrices.